2020
DOI: 10.5152/tjg.2020.19510
|View full text |Cite
|
Sign up to set email alerts
|

Hearing evaluation with ABR in pediatric patients with celiac disease

Abstract: Serum resolvin D1 levels as a marker of inflammation in constipation dominant irritable bowel syndrome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…15 This conclusion is mirrored by Bükülmez et al 16 with a study with large sample size (97 children with CD and 85 controls) that showed no significant difference in pure tone audiometry, tympanometry, speech audiometry, or OAE between patients with CD and controls. A further 3 studies, 17-19 similarly designed, also drew the same conclusions that SNHL and CD show no association, with one of those studies demonstrating objective evidence of no difference by using auditory brainstem responses. 19…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…15 This conclusion is mirrored by Bükülmez et al 16 with a study with large sample size (97 children with CD and 85 controls) that showed no significant difference in pure tone audiometry, tympanometry, speech audiometry, or OAE between patients with CD and controls. A further 3 studies, 17-19 similarly designed, also drew the same conclusions that SNHL and CD show no association, with one of those studies demonstrating objective evidence of no difference by using auditory brainstem responses. 19…”
Section: Discussionmentioning
confidence: 84%
“…A further 3 studies, 17-19 similarly designed, also drew the same conclusions that SNHL and CD show no association, with one of those studies demonstrating objective evidence of no difference by using auditory brainstem responses. 19…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…On the contrary, Bukulmez et al 13 observed similar hearing functions of children with newly diagnosed CD and healthy controls. Other studies from Urgnaci et al 14 Sahin et al 15 Yazici et al 16 and Yaprak et al 17 did not show significant SNHL in overall measurements of patients with CD compared with controls and hypothesized that subclinical SNHL should be investigated in CD patients for recognizing hearing loss early during the course of the disease.…”
mentioning
confidence: 92%